Education in Lebanon from the era of AL-Mutasarifiyah to the declaration of the Republic: (Historical study) - Abd, Abdel-Khaleq Mohamed; Kadhim, Qahtan Hamed (Al-Adab Journal, 2022)
Lebanon is the city of culture and books, where schools have emerged and the number of intellectuals has even competed among themselves to seek knowledge. Lebanese families encouraged their children to ride the wheel of scientific progress despite the difficult life and expensive study materials. Lebanon became the focus of European countries, especially France, which counted it as its capital. The East devoted its efforts and efforts to developing educational curricula that represent its interests and policies in the region. It succeeded in its educational endeavor and resulted in the presentation of brilliant political and cultural figures who managed to lead the state of Lebanon and isolate it from its Arab and national surroundings. In general, and French in particular.